Pengelolaan Koperasi Canggu Beach Transport Sebagai Wadah Pengusaha Angkutan Umum Pariwisata di Echo Beach Canggu Badung - Ni Made Sumiati; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2017)
The growth of tourism industry is a push to growth of community’s creativity in developing their potential, by utilizing the opportunities created from the presence of tourism, such as tourism public transport servicesthat is created by Koperasi Canggu Beach Transport. This studyaims to know the management applied as well as the strenght and weakness of implementation. The research method that used to identify the management of tourism public transportservice in Cangguis qualitative data and quantitative data obtained using the techniques of observation, interview and literaturestudy. Purposive sampling is used to determine the informants. The result of this study concluded that the management of Koperasi Canggu Beach Transport has been appropriate according to planning and organizing which done before. Monthly meetings are held in an effort to control and evaluate the result of the project that already done. There are some suggestionsto create new queue system that applied and also needed an increasement of socialization through social media to introduce and also as a promotion media. . Keywords:Tourism, Management,Tourism Transport Mode,Transportation